Primary Hepatoid Adenocarcinoma of Gallbladder With MB21D2/GALNT12/ARID2 Mutations: A Case Report - Li, Zhenyu; Jiang, Qingming; Chen, Xinyu; Xiao, Yu; Xiao, Jue (Frontiers in Endocrinology, 2022)
Background Primary hepatoid adenocarcinoma of the gallbladder is a relatively rare type of extrahepatic adenocarcinoma. The genetic changes involved in this type of adenocarcinoma were unexplained so far. We reported a rare case of primary hepatoid adenocarcinoma of gallbladder with Mab-21 domain containing 2 (MB21D2), polypeptide N-acetylgalactosaminyltransferase 12 (GALNT12), and AT-rich interaction domain 2 (ARID2) mutations, which was confirmed after surgical resection pathologically. Case Summary A 69-year-old female with distention of hypogastrium and constipation received enema treatment, but ineffectively. No abnormalities were found on relevant physical examination. Then, the CT and MRI demonstrated a 3.3–4-cm soft tissue mass shadow in the neck of the gallbladder. The primary lesions consisted of two components: high-grade intraepithelial neoplasia of glands and hepatoid glands microscopically after laparoscope cholecystectomy. Immunohistochemical staining showed the sameness and difference of the two areas. Furthermore, tumor mutational burden (TMB) shows that the MB21D2, GALNT12, and ARID2 genes were mutated. Conclusion This is the first report of primary hepatoid adenocarcinoma of the gallbladder with MB21D2, GALNT12, and ARID2 mutations. This will provide a theoretical basis for genetic changes in rare tumors.